Virus‐like particles for vaccination against cancer - Mona O. Mohsen (4056964) (2019)
Active immunotherapy of cancer aims to treat the disease by inducing effective cellular and humoral immune responses. Virus‐like particle‐based vaccines have evolved dramatically over the last few decades, greatly reducing morbidity and mortality of several infectious diseases and expectedly preventing cervical cancer caused by human papilloma virus. In contrast to these broad successes of disease prevention, therapeutic cancer vaccines remain to demonstrate clinical benefit. Yet, several preclinical and clinical trials have revealed promising results and are paving the way for medical breakthroughs. This study reviews and discusses the recent preclinical development and clinical trials in this field. Other Information Published in: WIREs Nanomedicine and Nanobiotechnology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/wnan.1579